Peran Guru dalam Membentuk Perilaku Siswa di SMA Muhammadiyah Kupang - Wan Azizah; Ahmad Atang (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2023)
This study aims to determine the teacher’s role in shaping student personality, and the constraints of the teacher’s role in shaping student personality at SMA Muhammadiyah Kupang. This type of research is qualitative methods. The subjects in this study were teachers and students. The techniques used in collecting data in this study are through observation, interview, and documentation. The data analysis techniques used data reduction, data presentation, and conclusion. The results of this study indicate that the role of the teacher is as a teacher guide (finding, directing, motivating), as a role model for giving (attitude, speech, behaviour, mental, morals, good morals), the teacher has carried out its role but, in its implementation, it is less effective, so that the formation of the student’s behaviour has not been achieved. The obstacles teachers face in shaping student behaviour are the negative influence from various social media, lack of family attention, and bad friends associating with students, the teacher has tried but has not succeeded in implementing it.